Analysis of tensions intrinsic to Medically Assisted Procreation through gamete donation based on the Pragmatic Sociology perspective (Brazilian Journal of Health Research, 2019)
Introduction: Medically assisted procreation (MAP) through gamete donation not only triggers scientific, moral, political, social and religious debates; it concerns personal involvement in close relationships. Objective: Analyzing the visible or invisible controversies, tensions and constraints regarding MAP involving third-part donors in France and Portugal. Methods: In total, 66 interviews were conducted with a different set of actors for the present project. These actors were directly linked to MAP techniques, either because they looked for them (heterosexual and homosexual couples) or because they were responsible for their implementation (specialists in reproductive medicine and embryology) or for discussions and regulations about them (deputies / senators and members of ethics committees). We interviewed 20 beneficiaries (ten in France and ten in Portugal) and 46 professionals (22 in France and 24 in Portugal). Results: The ten women interviewed in the two countries pointed out biographical and care trajectory similarities in the succession of trials to overcome their infertility experience. All these women had heterosexual marriages, were in the age group 34 - 43 years, worked in the tertiary sector and had higher education, except for two cases (complete secondary education). It was possible exploiting the tensions and commitment that have emerged between partners who have chosen MAP with third-part donors due to infertility issues. Conclusion: It is possible to standardize and regulate the MAP procedure with third-part donors. However, even if couples have volunteered to participate and manifest process secrecy, the tension remains because it is constitutive of the object.